Memperkuat Kompetensi ASN Melalui Pendekatan Non Klasikal: Menuju Aparatur Negara Yang Adaptif Dan Berkinerja Tinggi - Sukirno, Nurachma Indrati (Fakultas Ekonomi dan Bisnis Universitas Islam DR KH EZ Mutaqien, 2025)
Competency development is important for improving State Civil (ASN) performance to make public services as the government output becomes faster, more precise, and affordable. ASN competency development currently still refers to the classical approach which emphasizes face-to-face. This method has several weaknesses, including requiring adequate resources such as teachers, budget and infrastructure, while the the government resources are limited. The purpose of this study is to identify new approaches, especially non-classical approaches that are effective in developing ASN competencies and to analyze the impact of implementing non-classical approaches on ASN performance. By using qualitative research methods with descriptive analysis of data, documents, literature and laws and regulations, it shows that ASN competency development using non-classical methods has advantages compared to classical methods. Non classical methods are also proven in improving ASN competencies in terms of knowledge and digital literacy which have an impact on improving ASN performance and adaptation to technological developments.